Penerapan Lean Production pada Penggilingan Bahan Tepung Tapioka untuk Mereduksi Pemborosan di Kelurahan Cimahpar - Dedeh Ratnanengsih; Sazli Tutur Risyahadi; Hendri Wijaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Waste in micro small and medium enterprise of tapioca flour milling is caused by inefficient production process flow. Lean production is manufacture concept to produce efficient product.The purpose of implementing lean production is to reduce waste in order increase product value.Waste is analyzed using value stream mapping. This method is used to determine the flow of theprocess from the beginning of the raw material to produce a product, so that it can be determinethe cause of waste at each stage of the production process. Result from this study show that thetapioca materials milling processing efficiency of 62.38%. The wastes found in the form ofunnecessary motion, waiting, transportation, and defect. The improvement so that waste can bereduced is by applying 5S work culture, visual management and standard operating procedures. Keywords: lean, production, tapioca, waste